(untitled) (KYAMC Journal, 2019)
Background: Incisional hernia is a common complication of abdominal surgery. The success and postoperative outcomes of hernia repair depends upon many factors and out of these, the size of the hernial defect plays an important role. Objectives: To determine whether the size of the hernia defect had any impact over post-operative outcomes following prolene mesh repair of incisional hernia. Materials and Methods: Total 52 patients of incisional hernia who underwent prolene mesh repair by onlay technique were selected in this study. Patients were divided into three groups according to the size of hernial defect, as <5cm (small group), 5-10 cm (medium group) and >10cm (large group). Result: Respiratory problems were observed in 3 (42.9%) out of 7 subjects of hernial defect size >10 cm and 2 (6.2%) Out of 32 subjects of hernial defect size 5-10 cm. No subject of hernial defect size <5cm had respiratory problem. Wound infection was observed in 2 (15.4%) out of 13 subjects of hernial defect size <5 cm, 3(9.4%) Out of 32 subjects of hernial defect size 5-10 cm and 4(57.1%) out of 7 subjects of hernial defect size >10 cm. Pain was persistent in 3(5.8%) out of 52(100%) subjects more than 6 months after hernioplasty where 2 (28.6%) out of 7 subjects of hernial defect size >10 cm and 1(3.1%) out of 32 subjects of hernia defect size 5-10 cm. So, larger hernial defect was significantly associated with more pain persistence (p= 0.019). Conclusion: Larger hernial defect is associated with more post-operative complications and increase morbidity. KYAMC Journal Vol. 10, No.-1, April 2019, Page 2-6